Stenting as a palliative method in the management of advanced squamous cell carcinoma of the oesophagus and gastro-oesophageal junction - Janusz Wlodarczyk; Jarosław Kużdżał (Videosurgery and Other Miniinvasive Techniques)
Advanced squamous cell carcinoma of the oesophagus and gastroesophageal junction usually requires palliative treatment, and the method of choice is stenting. There are several types of stents currently available, including: self-expandable metallic stents (fully or partially covered); self-expandable plastic stents; biodegradable stents. Each of the mentioned stents has its advantages and limitations, and requires a proper, patient-tailored selection. Due to the close anatomical relationship between the oesophagus and bronchial tree, some patients may require bilateral stenting. Oesophageal stenting may not only be considered as a palliative procedure, but can also be implemented to alleviate dysphagia during preoperative chemotherapy and/or radiotherapy.